AI in Education: Impact on Learning Experiences and Outcomes at New Lambunao Integrated School - Legas, Michelle D.; Mamaril, DBA, DIT, Julius Cesar O. (Asian Journal of Multidisciplinary Studies, 2025)
This research explores the integration of Artificial Intelligence (AI) in education, focusing on its impact on learning experiences and academic outcomes at New Lambunao Integrated School. A mixed-method approach was used, combining a comprehensive literature review and a quantitative survey involving 50 students and 10 teachers from Junior and Senior High School levels. One of the most commonly used AI tools identified in the study is ChatGPT, which students and teachers utilize for personalized tutoring, automated assessments, and real-time support. Findings reveal that 75% of students and 70% of teachers regularly use AI-based educational tools, with over 80% acknowledging its positive impact on engagement and learning personalization. However, challenges such as limited internet access, lack of teacher training, and insufficient devices continue to hinder full integration. The study concludes that while AI tools like ChatGPT offer significant educational advantages, infrastructural and training support are essential for maximizing their potential in public school settings.